(untitled) (Journal on Excellence in College Teaching, 2024)
Team-based learning, or TBL, is an application-oriented teaching method that combines small- and large-group learning by incorporating multiple small groups into a large group setting. It has been increasingly used in postsecondary and professional education over the past two decades. Given this increasing usage, many faculty wonder about the effects TBL has on learning outcomes. The authors performed a review and synthesis on the educational literature with respect to TBL to examine the quality of their descriptions of core TBL elements, then constructed narrative summaries of these selected articles. Their analysis demonstrated early evidence of positive educational outcomes in terms of knowledge acquisition, participation and engagement, and team performance. The authors conclude that the TBL literature is at an important maturation point, where more rigorous testing and study of additional questions relating to the method are needed, as well as more accurate reporting of TBL implementation.